Analysis of the Concept of Compensation for Damage to ESAF Motorcycle Frames from Wahbah Zuhaily's Perspective (Case Study at the Medan City Honda Showroom) - Rizki Bagus Handoko; Ardiansyah (Warmadewa Press, 2024)
This research aims to analyze the concept of compensation for damage to the ESAF frame on motorbikes from Wahbah Zuhaily's perspective. The focus of this research is on a case study related to the issue of ESAF frame damage on Honda motorbikes in Medan City. The research method used is a qualitative approach with data collection techniques through interviews, observation, and literature study. The research results show that the concept of compensation in Wahbah Zuhaily's view regarding damage to the ESAF frame of a motorbike can be explained through the principles of Islamic law. Consumers, as motorbike owners, have the right to obtain compensation if the damage is caused by manufacturing defects or non-compliance with safety standards. The concept of khiyar (option or choice) in Islamic law gives consumers the freedom to choose between repairing damage, replacing the motorbike unit, or getting equivalent compensation. A case study at the Medan City Honda showroom shows that Honda motorbike owners who experienced damage to the ESAF frame have submitted compensation claims in accordance with the mechanism regulated by the company. However, there are challenges in handling compensation claims that need to be considered by the relevant parties. In conclusion, the analysis of the concept of compensation for damage to motorbike ESAF frames from Wahbah Zuhaily's perspective provides an in-depth understanding of the rights and responsibilities of consumers as well as the obligations of business actors in the context of product damage. This research is expected to provide conceptual and practical contributions to the understanding of Islamic law in the context of consumer protection related to damage to automotive products.